PENCIPTAAN MEDIA PROMOSI PURA MANGKUNEGARAN SOLO SEBAGAI UPAYA MENINGKATKAN MINAT KUNJUNGAN WISATAWAN MANCANEGARA - Harmanda, Brian; Fianto, Achmad Yanu Alif; Budiardjo, Hardman (Jurnal Art Nouveau, 2015)
Abstract: The purpose of creation of a media campaign Solo Mangkunegaran this is to preserve local cultural heritage. The study was conducted using qualitative research method is by conducting interviews, observation, documentation, and literature to obtain the data used to support conception. Data were analyzed using several stages, namely data reduction, data presentation, and conclusion. From the data analysis found some keywords that will be used to reach the intended target audience. After analyzing the data, found a concept or keyword of